2009
DOI: 10.1080/10400410902858683
|View full text |Cite
|
Sign up to set email alerts
|

Problem Finding and Contradiction: Examining the Relationship Between Naive Dialectical Thinking, Ethnicity, and Creativity

Abstract: This research examined the association between naive dialectical thinking and creativity, measured as originality in problem construction and reframing (types of problem finding). Ethnic identity (Caucasian vs. Asian=Asian American) was examined as a moderator. Two correlational studies and one experimental study revealed a complex pattern of results: For problems with low inherent contradiction, naive dialectical thinking decreased originality on problem finding tasks, whereas for tasks with higher contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 40 publications
3
50
0
1
Order By: Relevance
“…In this instance use of the six hats tool, which provides more conceptual information could help to scaffold thinking in more direct ways, which in turn may have a greater effect on performance. Though speculative, such a proposal would be consistent with the view that techniques that provide more structure can have a greater effect on performance (Paletz & Peng, 2009;Scott, Leritz, & Mumford, 2004a). Alternatively, or in addition to this complexity effect, it might be that there is a better match between the content of the tool and An issue not explored within this study but relevant to the field of training within CPS is the duration of any effects elicited by such training.…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…In this instance use of the six hats tool, which provides more conceptual information could help to scaffold thinking in more direct ways, which in turn may have a greater effect on performance. Though speculative, such a proposal would be consistent with the view that techniques that provide more structure can have a greater effect on performance (Paletz & Peng, 2009;Scott, Leritz, & Mumford, 2004a). Alternatively, or in addition to this complexity effect, it might be that there is a better match between the content of the tool and An issue not explored within this study but relevant to the field of training within CPS is the duration of any effects elicited by such training.…”
Section: Discussionsupporting
confidence: 50%
“…With this in mind it is no surprise that the easy-to-use tool proved most beneficial, though it should be noted that use of the six hats also led to greater originality relative to the placebo group. Nevertheless, a more ambiguous and/or ill-defined problem would be more difficult, requiring greater cognitive effort and as a consequence performance on a task utilising such a problem may be more influenced by a tool that provides greater conceptual information (see, Paletz & Peng, 2009). Hence it is possible that comparing the two tools (i.e., six men and six hats) on a problem construction task utilising a more complex problem may elicit a different pattern of effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contention that dialectical thinking aids creativity has been supported by research by Wu and Chiou (2008), who found a positive correlation between dialectical thinking and performance on a divergent thinking task in young Taiwanese adults. However, Paletz and Peng (2009) found that Asians and Asian-Americans received similar originality scores on a test of problem conceptualisation regardless of their tendency towards dialectical thinking, whereas Caucasians displayed a negative relationship between dialectical thinking and originality, which suggests that the relationship between dialectical thinking and creativity may be culture-specific. Wu and Chiou's (2008) research measured dispositional dialectical thinking; a more experimental approach could be useful.…”
Section: Problem Finding and Conceptualisationmentioning
confidence: 84%
“…Those in the control group were given an outline of what problem finding means along with the same example problem and some example restatements. The problem used in the main part of the study was the same for all participants: 'I am in a new city and need dinner', which was taken from Paletz and Peng (2009).…”
Section: Methodsmentioning
confidence: 99%